The Assessment of the Image of a Non-Public Higher School – A Case Study - Radosław Ryńca; Robert Łojko (Communications of International Proceedings, 2020)
The changes taking place on the market of educational services require changes in the way higher schools are managed. The key to success is to find and undertake solutions that will allow a higher school to maintain a good competitive position. It seems that image activities carried out by tertiary education institutions may be of great importance, as a result of which it will be possible to satisfy the needs and expectations of various higher school stakeholders. This article aims to present the assessment of the image of a non-public higher education institution as well as to offer the proposal of the improvement measures. Based on the surveys carried out, the authors identified the factors which have a decisive influence on the image of a higher school.
Keywords: Higher school image; higher school image improvement.